ZMIANY PARAMETRÓW MORFOMETRYCZNYCH JEZIORA STRZESZYŃSKIEGO - Choiński, Adam; Każmierska, Agnieszka (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
The paper analyses the changes in the Strzeszyńskie lake basin, located within the borders of the city of Poznań. The study was based on five topographic maps from the years: Moreover, the morphometric parameters of the basins from 1908, 1992 and 2013 were compared. Although the lake is located only a few kilometers from the center of Poznan, its basin has not changed significantly. Undoubtedly, this is influenced by the development of the lake basin. At present, however, there are symptoms indicating the worsening state of the waters.